The role of the agricultural sector in increasing economic growth from an Islamic economic perspective: A study in Deli Serdang Regency, North Sumatera Province, Indonesia - Tobing, Iqbal Fahri; Batubara, Maryam; Yusrizal, Yusrizal (Journal of Islamic Economics Lariba, 2024)
IntroductionThe agricultural sector is vital for economic growth in agrarian regions, particularly in Indonesia. Despite its substantial contributions to employment, food security, and regional GDP, the sector faces systemic challenges, including limited technological adoption and inadequate infrastructure. Islamic economics, emphasizing equity, sustainability, and social welfare, offers a promising framework for addressing these challenges.ObjectivesThis study explores the role of the agricultural sector in promoting economic growth in Deli Serdang Regency, North Sumatra, from the perspective of Islamic economics. It aims to assess the impact of government interventions and the potential of Islamic financial instruments, such as zakat and waqf, in enhancing agricultural productivity and sustainability.MethodA qualitative descriptive approach incorporated field observations, semi-structured interviews, focus group discussions, and document analysis. Data were analyzed using interactive qualitative analysis to identify themes and patterns, supported by triangulation to ensure reliability.ResultsThe findings reveal that agriculture remains a cornerstone of economic stability in Deli Serdang, contributing significantly to employment and regional development. Government interventions, including subsidies, infrastructure investments, and training programs, have improved productivity but face challenges in equitable implementation. Islamic economic principles, particularly the use of zakat and waqf, offer transformative potential by addressing financial and ethical dimensions of agricultural development.ImplicationsThis study highlights the need for a synergistic approach that integrates Islamic economics with government policies to revitalize agriculture sustainably. The findings contribute to the discourse on ethical and inclusive economic development, offering practical insights for policymakers and stakeholders.Originality/NoveltyBy integrating Islamic economic principles into agricultural development analysis, this study provides a unique framework for addressing systemic challenges while promoting sustainability and inclusivity in agrarian economies.